2013
DOI: 10.1016/j.juro.2013.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delayed Hematuria Following Photoselective Vaporization of the Prostate

Abstract: Delayed hematuria occurs commonly after photoselective vaporization of the prostate but severe hematuria is rare. Larger prostate size, longer followup and use of anticoagulation were associated with a higher risk of delayed gross hematuria while preoperative 5α-reductase inhibitor use and older age were protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
5
1
1
Order By: Relevance
“…On the other hand, the use of 5-ARI and older age were protective factor. 19 In our study, we did not see the difference in those parameters between bleeding-related ER visits or not within 3 months. A long-term follow-up after five transurethral procedures is needed.…”
Section: Dovepresscontrasting
confidence: 65%
“…On the other hand, the use of 5-ARI and older age were protective factor. 19 In our study, we did not see the difference in those parameters between bleeding-related ER visits or not within 3 months. A long-term follow-up after five transurethral procedures is needed.…”
Section: Dovepresscontrasting
confidence: 65%
“…Haemostatic properties have also been shown in patients with an increased haemorrhage risk (anticoagulation/ antiplatelets therapy, bleeding disorders) [20,21]; however, the retrospective nature of many studies and the inclusion of prostate sizes only between 50 mL and 110 mL make it difficult to come to strong conclusions [22]. Some studies have investigated factors potentially linked to postoperative bleeding, showing a higher rate in patients with larger prostate size [17], and those on anticoagulation [23] or who underwent multiple manual irrigations shortly after operation [24]. In this study we report our analysis of the risk of bleeding after discharge and its predictive factors in patients undergoing ThuLEP.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Chart review studies have suggested that risk factors for early postoperative gross hematuria following endoscopic prostate resection or vaporisation may include large prostate size, use of anticoagulation, and younger age, and the benefit of 5ARIs during this initial period is inconsistent. (8,9) We feel that the evidence for gross hematuria reduction in operation-naïve prostates(10) and during TURP(5) should not be automatically extrapolated to the post-TURP period. Given the lack of evidence supporting the use of 5ARIs after TURP, and their potential adverse effects(11) their use should be further evaluated in clinical trials specific to this clinical scenario.…”
Section: Discussionmentioning
confidence: 99%